Communication and attention dynamics: An attention‐based view of strategic change - Ocasio, William; Laamanen, Tomi; Vaara, Eero (Strategic Management Journal, 2018)
Research Summary : The attention‐based view (ABV) has highlighted the role of organizational attention in strategic decision making and adaptation. The tendency to view communication channels as “pipes and prisms” for information processing has, however, limited its ability to address strategic change. We propose a broader role for communication as a process by which actors can attend to and engage with organizational and environmental issues and initiatives and argue that such a view can significantly advance understanding of strategic change. On this basis, we offer suggestions for future research on communication practices, vocabularies, rhetorical tactics, and talk and text in shaping organizational attention in strategic change. We also maintain that this enhanced view of the ABV can help advance research on dynamic capabilities, strategy processes, strategy‐as‐practice, and behavioral strategy. Managerial Summary : To further enhance our capabilities to manage strategic change and renewal processes in organizations, we need a better understanding of how to manage organizational attention. In this article, we highlight the importance of understanding the role of communication and discuss the use of different communication practices, vocabularies, rhetorical tactics, and talk and text as possible levers that can be used to dynamically shape organizational attention. We call for further research to advance the understanding of how these levers can be used to influence the ways in which different sets of strategic issues, initiatives, and action alternatives are handled. We believe that such an enhanced view of organizational attention can enable the development of new, improved strategy practices to manage strategic change and renewal processes.